Intra‐patient variability in adalimumab drug levels within and between cycles in Crohn's disease. Issue 8 (27th February 2017) - Ward, M. G.; Thwaites, P. A.; Beswick, L.; Hogg, J.; Rosella, G.; Van Langenberg, D.; Reynolds, J.; Gibson, P. R.; Sparrow, M. P.
Summary: Background: Whether therapeutic drug monitoring for adalimumab needs to be performed at trough has not been defined. Aim: To determine intra‐patient adalimumab drug‐level variation and to identify modulating patient and disease factors. Methods: In this prospective observational study, adult patients with Crohn's disease established on maintenance adalimumab had drug levels measured repeatedly according to pre‐defined schedules (visit 1: day 4–6, visit 2: day 7–9, trough: day 13–14) across two consecutive fortnightly cycles. Disease activity was assessed using Harvey–Bradshaw Index, C‐reactive protein and faecal calprotectin. For this analysis, trough levels ≥4.9 μg/mL were considered therapeutic. Results: Nineteen patients underwent 111 evaluations. Mean intra‐patient drug levels from paired visits between cycles did not differ (visit1 cycle1: 4.81, cycle2: 5.21 μg/mL, P = 0.24, visit2 cycle1: 4.86, cycle2: 4.82, P = 0.91 and trough cycle1: 3.95, cycle2: 3.95, P = 0.99), irrespective of disease activity. Drug levels were stable over the first 9 days (visit 1–2), but declined to trough by a mean 1.06 and 0.89 μg/mL between visit 1 or 2, respectively ( P < 0.001). Models using nontemporal factors (smoking, syringe delivery device) and levels at earlier visits accounted for 66–80% of the variance in trough levels. On receiver‐operating curve analysis, thresholds identified in the first 9 days that predicted a therapeutic trough level were similar to the trough threshold itself, with high sensitivity but modest specificity. Conclusion: While therapeutic drug monitoring should be performed at trough, a drug level ≥4.9 μg/mL obtained during the first 9 days predicts a therapeutic trough drug level with reasonable confidence. Abstract : Linked Content This article is linked to Vande Casteele, Gils and Ward et al papers. To view these articles visit https://doi.org/10.1111/apt.14049 and https://doi.org/10.1111/apt.14091 .